Modelling and control of a grid-tied power conditioning unit for a megawatt fuel cell system - Ben Hamad, Khlid; Tariq Kahn, Mohamed (International Journal of Engineering and Technology, 2020)
It is a reality that future development in the energy sector is founded on the utilization of renewable and sustainable energy sources. These energy sources can empower to meet the double targets of diminishing greenhouse gas emissions and ensuring reliable and cost-effective energy supply. Fuel cells are one of the advanced clean energy technologies and have demonstrated their ability to be a decent substitute to address the above-mentioned concerns. They are viewed as reliable and efficient technologies to operate either tied or non-tied to the grid and power applications ranging from domestic, commercial to industrial. Among different fuel cell technologies, proton exchange membrane is the most attractive. Its connection to the utility grid requires that the power conditioning system serving as the interface between the stack and the grid operates accordingly. This study aims to model and control a power conditioning system for the grid-connection of a megawatt fuel cell stack. Besides the grid, the system consists of a 1.54 MW/1400 V DC proton exchange membrane fuel cell stack, a 1.3 MW/600 V three-level diode clamped inverter and an LCL filter which is designed to reduced harmonics and meet the standards such as IEEE 519 and IEC 61000-3-6. The power conditioning control scheme comprises voltage and current regulators to provide a good power factor and satisfy synchronization requirements with the grid. The frequency and phase are synchronized with those of the grid through a phase-locked-loop. The modelling and simulation are performed using Matlab/Simulink. The results show good performance of the proposed microgrid as well as the inverter design and control approach with a low total harmonic distortion of about 0.35% for the voltage and 0.19% for the current.Â Â Â